Odpowiedzi

2009-11-28T11:12:40+01:00
C)/x+2 1/7/-6/7≥0
1) 0</x+2 1/7/<0
a)x+2 1/7 >0
x>-2 1/7 zatem pod modułem mamy +
wtedy

x+2 1/7-6/7≥0
x+ 15/7-6/7≥0
x≥-9/7

b)x+2 1/7<0
x<-2 1/7
pod modułem -
-x-2 1/7 -6/7≥0
-x≥21/7/:(-1)
x≤3
Rozwiązanie : x∈<-9/7,3> - przedział domknięty obustronnie

d)/4 2/9-x/<7/9
warunek
0<4 2/9-x<0
a) 4 2/9-x>0
-x>-4 2/9
x< 4 2/9
Pod modułem +
4 2/9-x<7/9
-x< 7/9+38/9
-x<45/9
-x<5/:(-1)
x>5
b) 4 2/9-x<0
-x<-4 2/9
x> 4 2/9
Pod modułem -
- 4 2/9+x< 7/9
x< 7/9 - 38/9
x< -31/9
Rozwiązanie
x∈(-∞, -31/9) i (5 ,+∞)
e)/4/9+x/+1/10>0
warunek
0<4/9+x<0
a) 4/9+x>0
x>-4/9
pod modułem -
-4/9-x+1/10>0
-x> 40/90-9/90
`-x>31/90
x<-31/9
b) 4/9+x<0
x<-4/9 pod modułem +
4/9+x+1/10>0
x> -49/90
Rozwiązanie
x∈(-49/90 , -31,9)
f)/1 2/3-x/≤1 2/3
warunek0<1 2/3-x<0
a) 1 2/3-x>0
-x> -1 2/3
x< 1 2/3 pod modułem +
1 2/3-x≤1 2/3
-x ≤0
x≥0
b) 1 2/3-x<0
-x<-1 2/3
x> 1 2/3
pod modułem -
- 1 2/3 +x≤1 2/3
x≤2 4/3=3 1/3
Rozwiązanie
x∈<0 , 3 1/3>